Cognitive control in written word production - Neophytou, Kyriaki; Wiley, Robert W.; Rapp, Brenda (Frontiers in Language Sciences, 2024)
Cognitive control processes have been extensively studied in spoken word production, however, relevant investigations of written word production are scarce. Using data from a group of poststroke individuals we studied, for the first time, the neural substrates of cognitive control in written word production. We addressed three questions: Are control mechanisms (Question 1) shared by language and non-language domains; (Question 2) shared by lexical and segmental levels of word production within the word production system; (Question 3) related to both interference and facilitation effect types? To address these questions, we calculated cognitive control indices per individual, which reflected the interference and facilitation effects observed in written Blocked Cyclic Naming (written language production) and Simon (visuo-spatial processing) tasks. These behavioral cognitive control indices were studied both on their own, as well as in relation to the distribution of structural (gray matter) lesions. For Question 1, we provide strong evidence of domain-specific control mechanisms used in written word production, as, among other findings, distinct regions within Broca's Area were associated with control in written word production versus control in visuo-spatial processing. For Question 2, our results provide no strong evidence of shared control mechanisms for lexical and segmental levels of written word production, while they highlight the role of BA45 in instantiating control mechanisms that are specific to the two levels. For Question 3, we found evidence that BA45 supports distinct mechanisms associated with facilitation and interference, while orbital frontal cortex supports control process(es) associated with both. These findings significantly advance our understanding of the cognitive control mechanisms involved in written language production, as well as of the role of Broca's Area in cognitive control and language production more generally.